2009
DOI: 10.2146/ajhp080660
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a comprehensive, 24-hour emergency department pharmacy program

Abstract: A tertiary care teaching hospital successfully implemented a 24-hour, comprehensive ED pharmacy service that enhanced the efficiency and delivery of patient care and resulted in significant cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 6 publications
1
47
0
5
Order By: Relevance
“…More medication errors are reported with the presence of a pharmacist in the ED and the recommendations given by pharmacist have a high acceptance rate 15,16. One study completed in a rural ED showed a 66% difference in errors made before and after the implementation of an on-site clinical pharmacist 17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More medication errors are reported with the presence of a pharmacist in the ED and the recommendations given by pharmacist have a high acceptance rate 15,16. One study completed in a rural ED showed a 66% difference in errors made before and after the implementation of an on-site clinical pharmacist 17.…”
Section: Discussionmentioning
confidence: 99%
“…One study completed in a rural ED showed a 66% difference in errors made before and after the implementation of an on-site clinical pharmacist 17. A Veterans Administration study showed the cost avoidance realized of pharmacist presence in the ED to be $1.6 million per year based on interventions with a high probability to cause harm 15. Consultative activities led to the highest number of error interceptions, 25% of which are described as serious or life threatening 13.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Several studies have shown that clinical pharmacist provision of medication reconciliation reduces medication errors, saves costs associated with medication errors, and provides accurate documentation of patient medications. [11][12][13][14][15] As part of the American Society of Health System Pharmacist (ASHP) initiatives, pharmacist involvement in medication reconciliation is highly recommended. 16 However, medication reconciliation provided solely by pharmacists can …”
Section: Introductionmentioning
confidence: 99%
“…3 Available data have shown that pharmacists in the ED setting cannot only reduce the number of medication errors and provide a safer environment for patients but also potentially decrease the cost of treatment in the ED. [4][5][6] As a result, the American Society of Health-System Pharmacists (ASHP) and the Institute of Medicine recommend the inclusion of clinical pharmacists as a part of the emergency medicine care team to ensure safe, appropriate, and optimal medication therapy. 1,7 This recommendation has led to an interest in this specific practice area, as demonstrated by the findings of a recent survey, which showed that the number of hospitals that had a pharmacist assigned to and physically present in the ED increased from 3.4% in 2006 to 6.8% in 2008.…”
mentioning
confidence: 99%
“…The ED is an area primed for medication errors, and the presence of a pharmacist has been shown to increase patient recovery rates and decrease the incidence of medication errors. [3][4][5]11 While it is often a challenging task, we strive to develop systems that provide multiple safeguards to minimize the quantity and severity of errors in this often-chaotic environment. At our institution, we have invested significant time into developing order sets and physician and nursing education programs, redesigning automated dispensing cabinets, and altering our drug distribution process in an attempt to provide safer pharmacotherapy for patients in the ED.…”
mentioning
confidence: 99%